Strategies to mitigate secondary salinization in the Indus Basin of Pakistan: a selective review - Aslam, M.; Prathapar, Sanmugam A. (International Water Management Institute, 2006)
ThisThis report discusses the nature and causes of secondary salinization, reviews strategies developed and tested within IBIS to mitigate salinization, and identifies areas requiring further investigation.